Summary Isolation and diagnosis of some fungal types from external ear canal infection cases with sensitivity test to some antifungal agents - abdulshaheed, Dalya abulkareem (The Iraqi Journal of Veterinary Medicine, 2009)
This research included isolation of some types of fungi of molds and yeasts from cases of inflammation ofexternal ear canal in human from AL- yarmouk Teaching Hospital, by collection of 50 samples from males andfemales and from different ages during summer season , also 10 samples from non infected cases were taken ascontrol. Also sensitivity test of some isolates against some important antifungal agents which commonly usedin the treatments of infection of external ear canale cases.After cultivation of isolates on saboroud dextrose agar, diagnosed as follows :9 isolates of Aspergillus niger, 6 isolates of Aspergillus fumigatus, 3 isolates of Aspergillus flavus, one isolate ofAspergillus terrus, 10 isolates of Candida albicans, 5 isolates of Candida tropicalis, 2 isolates of Candidaparapsilosis.The results of the sensitivity tests of some isolates against the antifungal agents appeared as follows: the isolatesof Aspergillus spp. were very sensitive to Clotrimazole and Econazole, while were less sensitive againstNystatine.Whereas the species of Candida were very sensitive to Nystatine and Econazole, but less sensitive againstClotrimazole.